Engineering design process Find this title in WorldCat.org - Yousef Haik (Thomson/Brooks/Cole, 2003)
Engineering design process: Introduction; Design tools; Needs and goals; Market analysis and information gathering; Establishing functional structure; Specifications; Developing concepts; Concepts evaluation; Embodiment design; Cost analysis